From Experience to Traveler Loyalty: Examining the Moderating Role of Epistemic Motivation - Nguyen, Nam Danh (Journal of Posthumanism, 2025)
The study aims to determine the effect of experience on traveler loyalty through the moderation of epistemic motivation. It analyzes 256 usable responses using quantitative methods such as reliability testing, exploratory factor analysis, correlation analysis, and linear regression, following the hierarchical method and bootstrapping technique in Macro Process analysis on SPSS 26 software. The results indicate that peace of mind, outcome focus, service experience, and moments of truth positively impact traveler loyalty through the moderating role of cognitive engines. These findings highlight the strategic importance of linking experiences to enhance traveler loyalty in the context of an emerging economy. Based on the study’s results, some implications are provided to assist tourism enterprises in designing services that align with the cognitive characteristics of each customer, improve experience management efficiency, and foster more sustainable customer relationships.